Comparison of Lithium Ion and Lithium Polymer Performance as Solar Panel Energy Storage - Ilham Purnomo Aji; Hasti Afianti (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
Batteries have an important role in the development of energy needs. Good battery performance will support the devices it supports. The energy that can be stored in a battery is limited, so the battery will experience a cycle of charging and discharging. Improper charge and discharge processes can cause battery performance to decrease. Therefore, it is necessary to monitor battery performance in order to determine maximum battery performance. One of the aspects needed to monitor the state of charge and Depth of Discharge is to monitor the voltage, current and temperature on the types of lithium ion and lithium polymer batteries as energy storage for solar panels by using Arduino Atmega as a controller to determine the percentage of lithium ion and lithium polymer batteries and displayed on the LCD as HMI. From the results of comparing the performance of lithium ion and lithium polymer batteries, the results of SoC and DoD are measured and displayed on the LCD accurately, it can be seen which one is faster in charging time and lasts longer in use so that performance can be known of the two types of batteries.